The writer as storyteller? - Vaughan, Michael (My University, 1988)
In recent times, new schools of literary theory have appeared in South Africa. First came the materialists to challenge the liberal hegemony, and then the structuralists, who, in some of the later versions of theory, see the materialists themselves as too much wedded to liberalism and humanism. And then there is also Njabulo Ndebele, who seems to be something of a phenomenon in himself. Perhaps this is because he is African, not white. Literary theory in South Africa is, of course, largely monopolised by white academics, and this has no doubt, some consequences for the character of th resultant theory. It is noticeable, for example, with perhaps few exceptions, that materialist and structuralist theorists in South Africa derive their conceptual apparatus from the West, intact and ready-formed. All that remains is to apply it, as well as may be, to the local material. In other words, such local theorists art in an essentially pupilage relationship to the theorists of the West, who are vastly more sophisticated, inventive and original. Indeed, it could be said that the real theoretical work is being done in the West, and only imitated here, in a muffled sort of way. This is not said with the intention of deriding the efforts of local academics who attempt to grapple with and apply materialist and structuralist theories. I am, after all, one of those involved! There seems to be no other way, and this way does offer a certain scope. Imitation is never simply repetition, and perhaps this imitation is never, in any case, simply imitation. If local critical theory is derivative, this is a reflection on the nature of the relationship between South Africa and the West, on the nature of the South African education system, and on the separation of the upper reaches of the education system from the major realities of South African life. The separation of academic life from social life makes it very difficult, if not impossible, to be conceptually productive. All this is by way prelude to some consideration of the distinctiveness of Ndebele's contribution to literary theory in South Africa.....
African Studies Seminar series. Paper presented 7 March, 1988
Keywords: Ndebele, Njabulo S.; South African fiction (English). History and criticism